The effects of continuous sustainable land management practices on agricultural land productivity in Central Ethiopia - Alemu, Taye; Tolossa, Degefa; Senbeta, Feyera; Zeleke, Tesfaye (Brawijaya University, 2023)
The Ethiopian government has exerted efforts to rehabilitate degraded agricultural lands using a range of sustainable land management (SLM) initiatives to enhance agricultural productivity. One of the key components was improved structural soil and water conservation (SWC) technologies. This study examines the effects of continuous SLM practices on agricultural land productivity, with particular emphasis on SWC technology adoption in Central Ethiopia. The analysis was based on the data collected from 525 sample household surveys in two districts, namely Kewet and Sebeta-hawas. A propensity score matching (PSM) model was used to investigate the effects on treated and non-treated plots. The study findings revealed a substantial and positive effect on treated agricultural plots compared to non-treated ones in the Kewet district. At the same time, the difference was found positive but not significant in the Sebeta-hawas counterpart. The insignificant impacts are justified because SWC efforts focused on constructing structures rather than tailoring them with soil-replenishment and productivity enhancement functions. The important conclusion is that continuous SWC adoption efforts positively impact agricultural productivity; however, its effect is more noticeable when SWC structures are integrated with productivity enhancement functions and applied in low moisture areas. Thus, policymakers and project planners should consider the role of integrating physical SWC structures with soil replenishment and agronomic activities.